Leaching of Hemimorphite in Neutral Solution at High Temperature - Duoqiang Zhao; Shenghai Yang; Yongming Chen; Chaobo Tang; Jing He; Hao Li (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
The leaching behavior of hemimorphite in neutral solution (NH4+-Cl--H2O) was investigated at high temperature(T > 100 °C) under a range of experimental conditions. Thermodynamic calculations indicate that the tendency of dehydration of silica gel is significantly enhanced with increasing temperature. It is shown that the temperature, ammonium chloride concentration or L/S ratio increased resulted in a greater leaching efficiency. The following optimized leaching conditions were obtained: stirrer speed 400r/min, NH4Cl concentration 5.5M, L/S ratio 9mL/g at 160℃ for 3h. Under these optimized conditions, the average of zinc was 97.82%. The silicon was converted to quartz and remained in the residue. This process can be used to dispose willemite and hemimorphite as it solves the problem of silica gel dehydration.